2012
DOI: 10.1155/2012/109636
|View full text |Cite
|
Sign up to set email alerts
|

Gelam Honey Inhibits the Production of Proinflammatory, Mediators NO,PGE2, TNF-α, and IL-6 in Carrageenan-Induced Acute Paw Edema in Rats

Abstract: Natural honey is well known for its therapeutic value and has been used in traditional medicine of different cultures throughout the world. The aim of this study was to investigate the anti-inflammatory effect of Malaysian Gelam honey in inflammation-induced rats. Paw edema was induced by a subplantar injection of 1% carrageenan into the rat right hind paw. Rats were treated with the nonsteroidal anti-inflammatory drug (NSAID) Indomethacin (10 mg/kg, p.o.) or Gelam honey at different doses (1 or 2 g/kg, p.o.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 63 publications
0
94
0
2
Order By: Relevance
“…Studies have indicated the range of health benefits of honey, which includes anti-inflammatory, antioxidant and wound healing activities (Kassim et al, 2010;Mohamed et al, 2010;Al-Waili et al, 2011;Hussein et al, 2012). Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated the range of health benefits of honey, which includes anti-inflammatory, antioxidant and wound healing activities (Kassim et al, 2010;Mohamed et al, 2010;Al-Waili et al, 2011;Hussein et al, 2012). Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that honey flavonoid extract significantly suppressed the secretion of proinflammatory cytokines including tumor necrosis factoralpha (TNF-α) and interleukin (IL)-1 beta. 20 In an in vivo study on rats, Hussein et al 21 showed that honey could decrease edema and also decrease the levels of inflammatory mediators including prostaglandin E2, TNF-α, nitric oxide, and IL-6 in the plasma. Its anti-inflammatory effect was similar to that of indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…17 The antibacterial and anti-inflammatory effects of honey have been reported in several studies. [18][19][20][21][22][23] In addition, honey contains vitamin C concentration three times more than plasma, 24 which could accelerate tissue regeneration. 25 A recent clinical trial showed the effectiveness of honey as a dressing for dry socket.…”
Section: 5005/jp-journals-10024-2210mentioning
confidence: 99%
“…Paw edema induced by subcutaneous injection of λ-carrageenan into the right hind paw of rats, as was described previously by Hussein et al (2012). The anti-inflammatory effect of aqueous B. buceras extract was evaluated by decrease in percentage of inhibition of the paw thickness.…”
Section: Carrageenan-induced Paw Edema In Ratsmentioning
confidence: 99%
“…In this study would indicate that the inhibition of the paw edema could be due to its antioxidative and oxygen free radical scavenger properties. Edema is one of the fundamental actions of acute inflammation and is an essential parameter to be considered when evaluating compounds with potential anti-inflammatory activity (Hussein et al, 2012).…”
Section: Bucida Bucerasmentioning
confidence: 99%